EFL learners’ strategy use during task-based interaction in Second Life - Chen, Julian (ASCILITE, 2016)
Motivated by theoretical and pedagogical concerns that the link between second language (L2) learners’ second language acquisition (SLA) and language use in 3D multi-user virtual environments (MUVEs) is still not fully connected in current SLA literature, this study examined the patterns of English as a foreign language (EFL) learners’ employment of communication strategies during task-based interaction in Second Life (SL). Nine adult EFL learners worldwide were recruited, and they used their avatars to negotiate meaning with peers in interactional tasks via voice chat in SL. Results reveal that confirmation checks, clarification requests, and comprehension checks were the most frequently used strategies. Other types of strategy use were also discovered, such as a request for help, self-correction, and topic shift – accompanied by a metacognitive strategy and spell-out-the-word that had not been previously documented in task-based research in 3D MUVEs. This study demonstrated that SL could offer an optimal venue for EFL learners’ language acquisition to take place and prompt their cognitive processing during task-based interaction. Additionally, 3D multimodal resources afforded by SL provide additional visual support for EFL students’ input acquisition and output modifications. A call for more research on voice-based task interaction in 3D MUVEs is also needed.